1978
DOI: 10.1159/000458546
|View full text |Cite
|
Sign up to set email alerts
|

Mannosidosis: Separation and Characterization of Two Acid α-Mannosidase Forms in Mutant Fibroblasts

Abstract: Two acidic forms of a-mannosidase activity, A and B, are separated and characterized in fibroblasts from controls and patients with mannosidosis. In normal cells, A and B differ in adsorption on DEAE-cellulose, electrophoretic mobility, stability at 70 °C and resistance to freezing at -20 °C. In 5 of 6 mutant cell lines, A and B both exhibit altered Km’s for artificial substrates and decreased thermal stability. Zn^2+ has no effect on A or B in mutant or normal cells. In contrast, Co^2+ slightly inhibits B in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1981
1981
1995
1995

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In addition to clinical heterogeneity, biochemical and roentgenographic heterogeneity have been described. Burton & Nadler (1978) found variable Km's for amannose among mutant skin fibroblast cell lines suggesting multiple allelic variations in a-mannosidase. Some type I1 homozygotes have been shown to have only a partial deficiency of a-mannosidase (Bach et al 1978).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to clinical heterogeneity, biochemical and roentgenographic heterogeneity have been described. Burton & Nadler (1978) found variable Km's for amannose among mutant skin fibroblast cell lines suggesting multiple allelic variations in a-mannosidase. Some type I1 homozygotes have been shown to have only a partial deficiency of a-mannosidase (Bach et al 1978).…”
Section: Discussionmentioning
confidence: 91%
“…For example, several investigators have shown that normal a-mannosidase A and B were stimulated by zinc ions in vitro (37,38). Zinc also was found to enhance the residual acidic a-mannosidase activity in various sources from patients with mannosidosis (37)(38)(39)(40). However, a clinical trial of oral zinc supplementation did not alter the level ofresidual activity in plasma, leukocytes, or tears from the treated patients (41).…”
Section: Discussionmentioning
confidence: 99%
“…An inherited deficiency of acidic (~-mannosidase (A and B) causes the lysosomal storage disease in which cytosolic and Golgi mannosidases are unaffected (Carroll et al, 1972;Andria and Sly, 1981). The properities of the residual acid c~-mannosidase in human and cattle have been studied in tissue homogenates and cultured fibroblasts (Beaudet and Nichols, 1976;Desnick et aI., 1976;Philips et al, 1977;Burditt et al, 1978;Burton and Nadler, 1978;Poenaru et al, 1980;Ben-Yoseph et al, 1982). This residual activity showed abnormally high K m for the fluorogenic substrate and decreased thermal stablity.…”
Section: Time (Mi Nutes)mentioning
confidence: 99%